2014
DOI: 10.1111/bju.12807
|View full text |Cite
|
Sign up to set email alerts
|

Differences in 24‐h urine composition between nephrolithiasis patients with and without diabetes mellitus

Abstract: ObjectivesTo examine the differences in 24-h urine composition between nephrolithiasis patients with and without diabetes mellitus (DM) in a large cohort of stone-formers and to examine differences in stone composition between patients with and without DM. Patients and MethodsA retrospective review of 1117 patients with nephrolithiasis and a 24-h urine analysis was completed. Univariable analysis of 24-h urine profiles and multivariable linear regression models were performed, comparing patients with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 24 publications
(34 reference statements)
3
14
0
2
Order By: Relevance
“…A slightly increased risk of stone formation has been found in adults with DM compared to those without DM . One study of patients with a history of nephrolithiasis found stone‐promoting urinary differences in those with DM compared to those without DM, including lower pH, higher urinary oxalate, uric acid, and super saturation of calcium oxalate …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A slightly increased risk of stone formation has been found in adults with DM compared to those without DM . One study of patients with a history of nephrolithiasis found stone‐promoting urinary differences in those with DM compared to those without DM, including lower pH, higher urinary oxalate, uric acid, and super saturation of calcium oxalate …”
Section: Discussionmentioning
confidence: 99%
“…23 One study of patients with a history of nephrolithiasis found stone-promoting urinary differences in those with DM compared to those without DM, including lower pH, higher urinary oxalate, uric acid, and super saturation of calcium oxalate. 24 The etiology of stone formation during pediatric DKA is unknown, though it is not surprising that DKA may increase the risk of stone formation as dehydration, acidosis, and hyperglycemia with resultant glucosuria all promote hypercalciuria. Hypercalciuria is a known risk factor for nephrocalcinosis, has been reported in 26% of children with nephrolithiasis, 22 and occurs with increased incidence in children with DM.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Urine composition might be an important factor for the increase of stone formation in patients with DM. [ 3 4 ] Several studies had demonstrated that diabetic patients with kidney stones excreted more oxalate and uric acid, and had lower urine pH values than those of non-diabetic cohort. [ 3 4 ] However, these studies only included patients with history of nephrolithiasis, thus the results might not be applicable to the non-stone forming population.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 4 ] Several studies had demonstrated that diabetic patients with kidney stones excreted more oxalate and uric acid, and had lower urine pH values than those of non-diabetic cohort. [ 3 4 ] However, these studies only included patients with history of nephrolithiasis, thus the results might not be applicable to the non-stone forming population. There was only one study that looked at the composition of 24-h urine specimens in diabetic patients and normal volunteers who were not stone formers.…”
Section: Introductionmentioning
confidence: 99%
“…Останні, з одного боку, можуть бути факторами ризику для розвитку СКХ, а з іншого, утруднюють проведення необхідного оперативного лікування, потребують особливого, ретельного підходу до вибору лікувальної тактики, направленої на мінімізацію травматичності. Так, багато авторів [12,13] відмічають високу частоту розвитку нефролітіазу (97,7%) у хворих на цукровий діабет 2 типу, що, можливо, пов'язано із зменшенням антикристалоутворюючих властивостей сечі при цьому захворюванні. У ряді досліджень [16] відмічається зв'язок між надлишковою вагою і формуванням конкрементів, що може бути пов'язано із схильністю тучних людей до вживання великої кількості білка в поєднанні з відносно малим об'ємом випитої рідини.…”
Section: вступunclassified